ANALISIS EFISIENSI TEKNIS BANK PEMBANGUNAN DAERAH DI INDONESIA PERIODE TAHUN 2008 – 2009 DENGAN MENGGUNAKAN METODE DEA (DATA ENVELOPMENT ANALYSIS) - Amrina Rosyada (Media Ekonomi, 2011)
The purpose of this research is to acknowledge the level of efficiency from Regional Development Bank (Bank Pembangunan Daerah)/BPD) in Indonesia. This research use non - parametric approach which is DEA (Data Envelopment Analysis), to measure the efficiency of input and output of the Regional Development Banks. The input variables include are interest expense, administration and public expenses and salary expenses and the output variables are interest net income and other operasional income. The research concluded shows that the performance of the technical efficiency of banks BPD is not all reach the level of 100% and showed a fluctuation grow from 2008 – 2009. Pursuant to the technical efficiency level showed that there are 4 banks from 26 existing banks are showing a maximum efficiency. While the remaining 21 BPD banks fluctuating during 2008 to 2009. Keywords : Efficiency, Data Envelopment Analysis (DEA), Regional Development Bank